The Effects of Oil Price on Energy Production and the Ecuadorian Economy - Cevallos-Mina, Mirna Geraldine; Lara-Tambaco, Rosalba Mercedes; Reyes-Vera, Carlos Humberto; Mosquera-Quiñonez, Erick Fabián; Castillo-Gámez, José Luis (International Journal of Energy Economics and Policy, 2024)
Through an empirical analysis of the impact of variations in the international price of oil on the economic production of different strategic sectors and on energy production from various sources in Ecuador, the study seeks to show evidence on the economic effects of the price of oil. in a Latin American economy strongly linked to oil production. For this, relevant data were collected on production in different economic sectors, on the type of ownership in oil production and on energy production in various energy sources in Ecuador and statistical analyzes were carried out to evaluate the relationships between these and the international oil price. The results indicate that the effect of the oil price varies between the economic sectors of Ecuador. Some sectors, such as financial services and construction, show positive responses, while others, such as agriculture and fishing, appear less affected. The oil and mining sector in Ecuador is strongly linked to variations in the price of oil. The positive and significant response of the Oil and Mines GDP underlines the sensitivity of this sector to changes in international prices. Furthermore, energy production in Ecuador exhibits heterogeneous responses to variations in the price of oil. Forms of energy such as wind, solar, and thermal energy show positive and significant responses, while hydropower presents a negative response in some periods. Positive responses in forms of energy such as wind, solar, and thermal may indicate that the increase in the price of oil positively influences investment decisions in these energy sources. The study provides a significant contribution to the field of energy economics in oil-exporting countries and, particularly, in developing countries, as well as highlights the importance of energy diversification for these types of economies.